Psychiatric and physical rehabilitation intensive approach for suicide attempters by jumping from heights. - Rosso, Gianluca; Aragno, Elena; Capuzzo, Valeria; Gamna, Federica; maina, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Suicide is an important public health problem and one of the leading causes of death worldwide. Suicide behavior is influenced by interacting biological, psychological, environmental and current situational factors. One of the most important components modulating the risk of suicide as well his prevention is mental health: it is estimated that up to 90% of individuals who attempt suicide meets the criteria for a psychiatric disorder. Multiple other factors, such as physical illness, can be related to suicidal behaviors. Medical disorders may themselves be associated with an increased risk of suicide or be consequence of violent suicide attempts such as jumping from height. Providing optimal treatment for patients with suicidal behaviors, especially if violent, involves multiple treatments that may include psychiatric, psychological and physical therapies. Using a case series approach, we describe an acute psychiatric treatment program combined with intensive rehabilitation therapy in patients hospitalized for violent suicide attempts caused by jumping from height. The patients were treated through a multidisciplinary, simultaneous and integrated care program made up of a team of psychiatrists and physiatrists who work dynamically together with a flexible approach based on the specific clinical characteristics of each patient.